Transparencia para su explotación: gobiernos intermedios español y mexicano - Curto Rodriguez, Ricardo (Perfiles Latinoamericanos, 2023)
España y México son países fuertemente descentralizados y potencias en datos abiertos. Por ello, valoraremos a nivel de sus gobiernos intermedios (comunidades autónomas y estados, respectivamente) la transparencia activa de sus portales open data, que son los que albergan información realmente reutilizable. Tras la revisión de 18 000 conjuntos de datos, podemos afirmar que existe un mayor desarrollo de repositorios regionales en España y de datasets relativos a la rendición de cuentas, y que solo se identifica un caso de éxito: el País Vasco.
Transparency for its exploitation: Spanish and Mexican intermediate governments
Spain and Mexico are strongly decentralized countries and powerhouses in open data. For this reason, we will assess at the level of their intermediate governments autonomous communities and states, respectively) the active transparency of their open data portals, which are the ones that house truly reusable information. After reviewing 18 000 data sets, we can affirm that there is a greater development of regional repositories in Spain than in Mexico in terms of data sets related to accountability and that only one success case has been identified, País Vasco.
Keywords: España; México; transparencia; rendición de cuentas; datos abiertos; gobiernos regionales; Spain; Mexico; transparency; accountability; open data; regional governments; Scopus; WOS